Biosynthesis of 130-kilodalton mosquito larvicide in the cyanobacterium Agmenellum quadruplicatum PR-6. - Angsuthanasombat, C (1989)
The 130-kilodalton mosquito larvicidal gene, cloned from Bacillus thuringiensis var. israelensis, was introduced into the cyanobacterium Agmenellum quadruplicatum PR-6 by plasmid transformation. Transformed cells synthesized 130-kilodalton delta-endotoxin protein and showed mosquito larvicidal activity. Results demonstrate a potential use of a cyanobacterium for biological control of mosquitoes.